The light in the forest - Richter, Conrad, 1890-1968. (New York : Fawcett Juniper, 1991)
After being raised as an Indian for eleven years following his capture at the age of four, John Butler is forcibly returned to his white parents but continues to long for the freedom of Indian life.
Wilson's Fiction.
Wilson's Junior High School.
Wilson's Senior High School.
7.6
5-8
7-9
Keywords: Delaware Indians -- Fiction; Indians of North America -- Fiction; Delaware Indians -- Fiction; Native Americans -- North America -- Fiction